PWE-023 Should patients with ida have routine ileo-colonoscopy? data from capsule endoscopy. (22nd June 2015) - Neilson, LJ; Dunn, S; Panter, S
Abstract : Introduction: Video capsule endoscopy (VCE) is appropriate for patients with iron deficiency anaemia (IDA) who do not respond to oral iron replacement following normal upper and lower gastrointestinal endoscopy. 1 Terminal ileal (TI) intubation at the time of colonoscopy has a significant diagnostic yield in patients with IDA. 2 Bidirectional endoscopy without ileoscopy may miss significant lesions later noted by VCE. Method: This study aimed to identify what proportion of patients had TI pathology within the reach of the colonoscope and to assess whether ileo-colonoscopy would have prevented the need for VCE. Patients with VCEs for IDA at a single site between Jan 2009 – Dec 2014 were identified. Data were collected retrospectively, including previous colonoscopy findings and extent, VCE findings and subsequent colonoscopy findings. Results: 120 patients were identified, of which only 28 (23.3%) had TI intubation at colonoscopy. 5/28 (17.9%) demonstrated TI pathology at colonoscopy (4 ulceration, 1 inflammation). 23/28 (82.1%) had normal TI at initial colonoscopy, but 3 of these patients had ulceration in TI on VCE. 11 (9%) patients had TI pathology on VCE (6 normal TI, 4 TI ulceration, 1 TI inflammation), possibly within reach of ileo-colonoscopy. All 11 patients had undergone colonoscopy prior to VCE- 8/11 to TI, 5 of which were abnormal. Of those who had positive ileo-colonoscopy findings, VCE changed management in 2 additional cases (40%). 3 patients with TI pathology on VCE had not undergone ileo-colonoscopy. 1/3 (33.3%) of these patients was found to have a definite TI abnormality at subsequent ileo-colonoscopy and was treated for Crohn's. A cause for IDA was found at VCE in 37/120 patients overall (30.8%). 29/109 (26.6%) VCEs with no TI pathology revealed a cause for IDA, compared with 8/11 (72.7%) where TI pathology was found. Conclusion: In this cohort, only 5/37 (13.5%) of cases of IDA would have been diagnosed by ileo-colonoscopy and only one capsule endoscopy avoided by ileoscopy being performed. These data suggest that ileo-colonoscopy should be performed in cases of IDA but should not alter plans for VCE. A further prospective study is planned. Disclosure of interest: None Declared. References: Goddard AF, James MW, McIntyre AS, et al . Guidelines for the management of iron deficiency anaemia. Gut. 2011;60:1309-16 Neilson LJ, Bevan R, Panter S, et al . Terminal ileal intubation and biopsy in routine colonoscopy practice. Expert Rev Gastroenterol Hepatol . 2015 Jan 12:1-8. (accessed online 18/02/2015)